(untitled) (Physical Education, Health and Social Sciences, 2025)
This qualitative study explores the experiences and perceptions of English as a Second Language (ESL) instructors in higher education institutions in Pakistan regarding the use of Artificial Intelligence (AI)-powered tools in language instruction. Aiming to address the research gap in the literature on AI integration in ESL instruction in Pakistan, this study examines the current integration of AI, identifies potential applications to enhance instructor performance and student learning outcomes, and explores the challenges and limitations associated with AI integration. Through semi-structured interviews with 15 ESL instructors, analyzed using thematic analysis, the study reveals that ESL instructors are increasingly interested in leveraging AI-powered tools to support language instruction, but face significant challenges in integrating them into their teaching practices. The findings highlight key benefits of AI integration, including enhanced student engagement, improved feedback, and increased efficiency in grading and assessment, as well as significant challenges, such as limited access to AI-powered tools, inadequate training and support, and concerns about the reliability and validity of AI-generated feedback